The Fenugreek Herbal Tea Product for Women’s Health - Mokhtar, Maisarah; Mohsin, Hannis Fadzillah; Abdul Wahab, Ibtisam (Universiti Teknologi MARA Cawangan Melaka Kampus Jasin, 2020)
This study explores the phytochemical review of a medicinal plant, called Trigonella foenumgraecum L. or fenugreek. It is known regionally as halba in Malay or hilbeh in Middle East. This traditional herb is used to treat dysmenorrhea, in the episodes of painful uterine contractions, during menstruation. Community retail outlets would provide this natural resource as polypharmacy, which involves a mixture of fenugreek and other herb, e.g. cinnamon. The pharmacological properties of the fenugreek were investigated, including antidiabetic, antioxidant, anti-inflammatory, anticancer and antimicrobial activities. Much information is available for this species, e.g. in the form of herbal capsule and tea product. From the literatures, laboratory experiments were conducted, in order to quantitatively validate the bioactive components. The isolation of its natural molecules, for example diosgenin, an important steroidal sapogenin, could be achieved without extraction. It is expected that fenugreek seeds could function as a mild galactagogue.